Allometric scaling of aerobic fitness outputs in school-aged pubertal girls - Werneck, Andre O. [UNESP]; Conde, Jorge; Coelho-e-Silva, Manuel J.; Pereira, Artur; Costa, Daniela C.; Martinho, Diogo; Duarte, Joao P.; Valente-dos-Santos, Joao; Fernandes, Romulo A. [UNESP]; Batista, Mariana B.; Ohara, David; Cyrino, Edilson S.; et al. (Bmc, 2019)
BackgroundThis study aimed to determine the allometric exponents for concurrent size descriptors (stature, body mass and fat-free mass) and also to examine the contribution of chronological age and pubertal status combined with above mentioned size descriptors to explain inter-individual variability in the peak of oxygen uptake (VO2peak) among girls during circumpubertal years.MethodsThe final sample included 51 girls (10.7-13.5years). VO2peak was derived from an incremental progressive maximal protocol using a motorized treadmill. Anthropometry included body mass, stature and skinfolds. Measurements were performed by a single trained observer. Sexual maturation was assessed as self-reported stage of pubic hair (PH) development. Static allometric models were explored as an alternative to physiological output per unit of size descriptors. Allometry also considered chronological age and sexual maturation as dummy variable (PH2 vs. PH3 and PH3 vs. PH4).ResultsScaling coefficients for stature, body mass and fat-free mass were 1.463 (95%CI: 0.476 to 2.449), 0.516 (95%CI: 0.367 to 0.666) and 0.723 (95%CI: 0.494 to 0.951), respectively. The inclusion of sexual maturation increased explained variance for VO2peak (55% for PH2 vs. PH3 and 47% for PH3 vs. PH4). Body mass was identified as the most prominent body size descriptor in the PH2 vs. PH3 while fat-free mass was the most relevant predictor combined with PH3 vs. PH4.ConclusionsBody mass and fat-free mass seemed to establish a non-linear relationship with VO2peak. Across puberty, inter-individual variability in VO2peak is explained by sexual maturation combined with whole body during early puberty and by sexual maturation and fat-free mass during late puberty. Additional studies need to confirm ontogenetic allometric models during years of maximal growth.
Keywords: Static allometry; Cardiorespiratory fitness; Body composition; Puberty growth spurt; Physical fitness